Evolution of an Apomixis-Specific Allele Class in Supernumerary Chromatin of Apomictic Boechera - Mau, Martin; Mandáková, Terezie M.; Ma, Xingliang; Ebersbach, Jana; Zou, Lifang; Lysak, Martin A.; Sharbel, Timothy F. (Frontiers in Plant Science, 2022)
Asexual reproduction through seeds in plants (i.e. apomixis) is a heritable trait and apomixis linked loci have been identified in multiple species. However, direct identification of genomic elements is typically hindered as apomixis linked loci are commonly found in recombination-suppressed and repetitive regions. Heterochromatinized elements, such as B chromosomes and other supernumerary chromosomal DNA fragments have long been known to be associated with asexuality in both plants and animals, and are prime candidate regions for the evolution of multiple apomixis factors controlling the individual elements of apomixis. Here we examined molecular evolution, gene regulation and chromosomal location of a male apomeiosis factor (UPG2), a long-noncoding RNA gene, in sexual and apomictic Boechera with and without male apomeiosis (i.e. balanced and unbalanced apomicts). We revealed the origin of the gene in the apomixis genome on an apomixis-specific, supernumerary heterochromatic Boechera chromosome (Boe1). UPG2 is active in the tapetum at male meiosis. We found allele classes specific to apomictic and sexual Boechera accessions and a third class that shares features of both and point to a convergent transition state. Sex alleles are found only in some of the sexual accessions, have higher nucleotide divergence and lower transcriptional activity compared to apo alleles. These data demonstrate selective pressure to maintain function of UPG2 for unreduced pollen formation in apomicts as the occasional transmission of the allele from unbalanced apomicts into sexuals leads to pseudogenization and functional decay of copies in sexuals.